2009
DOI: 10.1080/08927010903161299
|View full text |Cite
|
Sign up to set email alerts
|

The use of physicochemical methods to detect organic food soils on stainless steel surfaces

Abstract: Food processing surfaces fouled with organic material pose problems ranging from aesthetic appearance, equipment malfunction and product contamination. Despite the importance of organic soiling for subsequent product quality, little is known about the interaction between surfaces and organic soil components. A range of complex and defined food soils was applied to 304 stainless steel (SS) surfaces to determine the effect of type and concentration of soil on surface physicochemical parameters, viz surface hydro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(14 citation statements)
references
References 31 publications
1
12
0
1
Order By: Relevance
“…Physicochemistry of the coatings was determined as carried out by Whitehead et al (2009). Surface tension parameters for polar and apolar liquids were used to calculate physicochemical parameters (van Oss et al, 1990;van Oss, 1995;van Oss et al, 1986) with modifications as described in Whitehead et al (2009).…”
Section: Coating Production and Characterisationmentioning
confidence: 99%
“…Physicochemistry of the coatings was determined as carried out by Whitehead et al (2009). Surface tension parameters for polar and apolar liquids were used to calculate physicochemical parameters (van Oss et al, 1990;van Oss, 1995;van Oss et al, 1986) with modifications as described in Whitehead et al (2009).…”
Section: Coating Production and Characterisationmentioning
confidence: 99%
“…Welding process commonly provides greater roughness on stainless steel surfaces welded. Several studies have reported correlation between surface roughness and bacterial accumulation on surfaces (Whitehead et al, 2009;Wirtanen and Mattila-Sandholm, 1992). However, other studies have reported a lack of correlation between surface irregularities or roughness and the number of bacteria attached (Silva et al, 2008;Szlavik et al, 2012).…”
Section: Introductionmentioning
confidence: 97%
“…If further organic material, cells, minerals, cleaning deposits and other debris are deposited onto a surface, this may be known as organic fouling. In food processing, there is constant fouling of surfaces by the food components being processed and this fouling forms the layer onto which microorganisms subsequently adhere (Whitehead et al, 2009a). This organic material may also potentially provide nutrients for the residual microorganisms, enabling multiplication and an increase in contamination of the surface, providing that other conditions conductive to growth are available (Whitehead et al, 2009b).…”
Section: Introductionmentioning
confidence: 98%
“…However, it has been shown that the susceptibility of cells to biocides may be reduced by the presence of organic material on the surface (Aarnisalo et al, 2000;Bagge-Ravn et al, 2003;Gram et al, 2007). Retained organic material on a surface may also impede the recovery of cells and methods of detection (Whitehead et al, 2009a). One of the most common ways to evaluate cell viability on surfaces is to use a swabbing and serial dilution method.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation